An academic review of the first two volumes of the International Journal of Environment (IJE) - Boolaky, Mehraz; Sunkavalli, Surya P (International Journal of Environment, 2014)
DOI: http://dx.doi.org/10.3126/ije.v3i2.10646 International Journal of the Environment Vol.3(2) 2014: 345-353